PENERAPAN TEORI BELAJAR CLASSICAL CONDITIONING DAN OPERANT CONDITIONING DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI MADRASAH IBTIDAIYAH - Alip Rahadian; Wahidah Fitriani; Ahmad Jihad Bawadi (Institut Daarul Qur'an Jakarta, Indonesia, 2025)
Islamic Religious Education is a consciously designed and implemented effort to foster and care for students so that they are able to understand all aspects of Islamic teachings, internalize them in life goals, and then practice them in everyday life so that Islam becomes a way of life. The purpose of this study is to determine learning theories that are always closely related to the realm of psychology because discussing the learning process means discussing humans as individuals. The type of research used in this study is a qualitative research type with a descriptive analysis approach through library research. The results of the study show that according to Ivan Pavlov, the classical conditioning theory explains that new reflexes can be formed by presenting certain stimuli before the reflex appears. In the context of education, providing stimuli in the form of awards or prizes to students can increase their learning motivation. According to Skinner, operant conditioning is a form of conditioning where individuals produce responses or behaviors (called operants), which are learned through reinforcement from the environment. Operants can be words or actions that arise as a result of interaction with external situations. According to Albert Bandura, social learning theory in Islamic Religious Education (PAI) learning. This theory focuses on learning through observation (observational learning), where students learn by observing the behavior, attitudes, and outcomes experienced by the observed model. The integration of these two approaches (Classical and Operant Conditioning) provides practical advantages in Madrasah Ibtidaiyah: classical conditioning helps build emotional readiness and religious routines, while operant conditioning strengthens and maintains moral habits through well-designed consequences.